(untitled) (Journal of The Colloquium for Information Systems Security Education, 2017)
Identity theft losses are in the billions of dollars. The crime affects individuals and industry. It consumes valuable resources and results in higher costs across the board. Technical strategies to address the problem have had mixed effects. The focus of this work is to report outcomes from research that assessed two distinct educational methods that targeted identity theft at the college level. One mode of presentation is text-based while the other is game-based. Study data show that students exposed to information through the game-based approach scored better on the identity theft assessment than did their counterparts who experienced the same information through the text-based method. Also, game-based participants remained longer in the educational unit and reported greater satisfaction than their text-based counterparts. Digital educational game-based learning is in its infancy. FIT demonstrates the efficacy of this method in the field of cyber education.